2016
DOI: 10.3835/plantgenome2016.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Mapping of Leaf Rust Response in a Durum Wheat Worldwide Germplasm Collection

Abstract: Leaf rust (caused by Puccinia triticina Erikss. [Pt]) is increasingly impacting durum wheat (Triticum turgidum L. var. durum) production with the recent appearance of races with virulence to widely grown cultivars in many durum producing areas worldwide. A highly virulent P. triticina race on durum wheat was recently detected in Kansas. This race may spread to the northern Great Plains, where most of the US durum wheat is produced. The objective of this study was to identify sources of resistance to several ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 139 publications
7
79
1
1
Order By: Relevance
“…For association mapping, different panels were used. Two-hundred and eight members of the Andean Diversity Panel (ADP; Cichy et al, 2015) and 278 members of the Middle American Diversity (MDP; Moghaddam et al, 2016) were grown and phenotyped. Sequencing was performed in a diverse panel of 90 varieties representing six species were acquired from the National Plant Germplasm System (NPGS).…”
Section: Germplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…For association mapping, different panels were used. Two-hundred and eight members of the Andean Diversity Panel (ADP; Cichy et al, 2015) and 278 members of the Middle American Diversity (MDP; Moghaddam et al, 2016) were grown and phenotyped. Sequencing was performed in a diverse panel of 90 varieties representing six species were acquired from the National Plant Germplasm System (NPGS).…”
Section: Germplasmmentioning
confidence: 99%
“…Segregation data of pod shattering data (oven test proportion, force, and shattering in the field) as well as SNP markers in the I9S population have been deposited in the UC Davis Dash public database (doi: 10.25338/B8TW2N:Gepts et al, 2019; doi: 10.25338/B8ZG68: Parker et al, 2019).Genotype data for the Middle American Diversity Panel(Moghaddam et al, 2016) can be accessed at http://arsf tfbean.uprm.edu/beancap/research/. Genotype data for the Andean Diversity Panel can be accessed at http://arsftfbean.…”
mentioning
confidence: 99%
“…However, the resulting mapping resolution is comparatively low and typically produces a large confidence interval of 10 to 20 cM as a result of the limited number of recombination events occurring in the construction of biparental mapping populations (Li et al, 2010; Manichaikul et al, 2006; Zhu et al, 2008). On the other hand, association mapping explores functional variations within genetically diverse panels through linkage disequilibrium (LD) analysis, which is very efficient and effective for identifying new genes or confirming candidate genes (Aoun et al, 2016; Yu and Edward, 2006). Compared with linkage mapping, association mapping is able to identify historical recombination events in a given population, which improves mapping resolution.…”
mentioning
confidence: 99%
“…The vast majority of the officially named wheat rust resistance genes are based on control by a single (monogenic) or a few (oligogenic) resistance loci, although a few of them are based on truly polygenic quantitative trait loci (Ellis et al, 2014). Recent association genetics studies have indicated that polygenic resistance to wheat rust diseases is paramount (Bajgain et al, 2015; Maccaferri et al, 2015; Bulli et al, 2016; Aoun et al, 2016). Depending on the race composition in a field, environmental conditions for disease development, and the specific trait being measured (assessment method), the wheat rust pathosystem may provide the opportunity to study the effects of trait genetic architecture and assessment methods on GS prediction accuracy.…”
mentioning
confidence: 99%